APLIKASI TRANSAKSI PENJUALAN DAN PEMBELIAN BERBASIS ANDROID DENGAN MENGGUNAKAN APPSHEET PADA BISNIS KONVEKSI RUMAH JAHIT DAN BORDIR KIKA KOTA BANDUNG - apriani, nadia (Jurnal Komputer Bisnis, 2025)
This research aims to develop an Android-based sales and purchase transaction application using AppSheet at Rumah Jahit dan Bordir Kika in Bandung City. The previously used manual recording system caused several issues, such as recording errors, data loss, and difficulties in tracking transactions. The research method applies the Waterfall model, consisting of requirements analysis, design, implementation, testing, and maintenance. The application integrates Google Spreadsheet with AppSheet to record sales, purchases, and customer data in real time. The findings show that this application improves efficiency, accuracy, and data accessibility for MSME actors. Thus, the application can serve as a simple, cost-effective, and efficient solution to support the digitalization of MSMEs in the garment sector. Overall, the implemented system has proven effective in enhancing transaction recording efficiency and accuracy. The use of AppSheet is highly relevant for MSMEs, as it is user-friendly, cost-efficient, and accessible from mobile devices. It is expected that this application can become a practical solution for MSMEs in improving sustainable business data management quality. Kata kunci : Aplikasi, Appsheet, Waterfall, Android.